The Role of Law Students on Strengthening Village Human Resources in the Era of the Industrial Revolution 4.0 - Niravita, April (Universitas Negeri Semarang, 2019)
Law faculty students are now required to possess not only theoretical and scientific expertise but also practical skills. In many situations, they play a crucial role in directly assisting the community in resolving various legal issues, ranging from minor cases to complex and intricate matters. The demand for legal aid and assistance has become increasingly unavoidable, particularly amid the rapid advancements in information technology and the evolving landscape of the Fourth Industrial Revolution.